Very low 1/f barrier noise in sputtered MgO magnetic tunnel junctions with high tunneling magnetoresistance - COEY, JOHN (My University, 2012)
Low frequency 1/f barrier noise has been investigated in sputtered MgO magnetic tunnel junctions(MTJs) with a tunnelingmagnetoresistance ratio of up to 330% at room temperature. The lowest normalized noise parameter ? of the tunnel barrier reaches 2.5???10?12?2.1???10?11 ?m2, which is comparable to that found in MTJs with the MgO barrier grown by MBE or electron?beam evaporation. This normalized barrier noise is almost bias independent in the voltage range of up to ?1.2?V. The low noise level and high voltage stability may reflect the high quality of the sputtered MgO with a uniform distribution of defects in the MgO layer.
PUBLISHED
Keywords: Physics